Intensified organic carbon burial on the Australian shelf after the Middle Pleistocene transition. (15th June 2021) - Auer, Gerald; Petrick, Benjamin; Yoshimura, Toshihiro; Mamo, Briony L.; Reuning, Lars; Takayanagi, Hideko; De Vleeschouwer, David; Martinez-Garcia, Alfredo
Abstract: The Middle Pleistocene Transition (MPT) represents a major change in Earth's climate state, exemplified by the switch from obliquity-dominated to ∼100-kyr glacial/interglacial cycles. To date, the causes of this significant change in Earth's climatic response to orbital forcing are not fully understood. Nonetheless, this transition represents an intrinsic shift in Earth's response to orbital forcing, without fundamental changes in the astronomical rhythms. This study presents new high-resolution records of International Ocean Discovery Program (IODP) Site U1460 (eastern Indian Ocean, 27°S), including shallow marine productivity and organic matter flux reconstructions. The proxy series covers the interval between 1.1 and 0.6 Ma and provides insights into Pleistocene Leeuwin Current dynamics along the West Australian shelf. The large >45 m global sea level drop during the marine isotope stage (MIS) 22–24 is marked in our data, suggesting that the MPT led to large-scale changes in Indian Ocean circulation patterns and surface water conditions. We consider shelf exposure (and thus the "Sahul-Indian Ocean Bjerknes mechanism") as a possible key process to increase the upwelling of nutrient-rich sub-Antarctic Mode waters through the Leeuwin Undercurrent along the Australian shelf. We conclude that the shoaling of nutrient-rich lower-thermocline waters enhanced mid-latitude productivity patterns in the eastern Indian Ocean across the 900-ka event. Highlights: Organic carbon fluxes on the Australian Shelf increased after 900 ka BP. Leeuwin Current intensity was tightly coupled to sea level in the middle Pleistocene. Sea level changes decoupled alkenone/carbon and nannofossil fluxes on the shelf. Spectral analyses indicate high latitude forcing increased after 900 ka BP. Expanding sub-Antarctic mode waters forced productivity changes after 900 ka.